Excelling Green Supply Chain Management Practices Through Maturity Model: A Case Study of Fish 96 Company - Santini, Siti Cahya; Simatupang, Togar (Asian Journal of Social and Humanities, 2024)
This research aims to improve GSCM practices at Fish 96, an SME in tilapia aquaculture located in Bandung, West Java, Indonesia. It identifies and addresses some critical business issues regarding reducing the DOA rate, improving operational efficiency, and reducing environmental impacts. The literature review forms the theoretical basis of GSCM practices such as green procurement, manufacturing, distribution, and reverse logistics. A new GSCM maturity model is developed and validated with the case study of Fish 96, which eval_uates the company's current maturity levels and structured improvements. It assesses that Fish 96 stands at the initial stage in the journey of GSCM. Most practices are either nonexistent or at an initial point of implementation. The suggested maturity model includes five levels: Nonexistent, Aware, Intermediate, Advanced, and Sustainable, which represent a clear roadmap for Fish 96 to improve its GSCM performance. The research recommends adopting broad green practices across all supply chain dimensions, emphasising systematic strategies and enhanced supplier engagement by focusing on efficiency measures. With these recommendations, Fish 96 will contribute to reducing operational costs while reducing environmental impacts and improving social outcomes, thus improving the company's long-term sustainability and competitiveness.